2005
DOI: 10.1021/jp052793n
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Scaling Factors for ab Initio Vibrational Frequencies

Abstract: Vibrational frequencies determined from ab initio calculations are often scaled by empirical factors. An empirical scaling factor partially compensates for the errors arising from vibrational anharmonicity and incomplete treatment of electron correlation. These errors are not random but are systematic biases. We report scaling factors for 40 combinations of theory and basis set, intended for predicting the fundamental frequencies from computed harmonic frequencies. An empirical scaling factor carries uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
388
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(419 citation statements)
references
References 35 publications
26
388
1
4
Order By: Relevance
“…This is probably due both to deficiencies in the electronic-structure level of theory used and to the neglect of anharmonicity, since the harmonic approximation is inherent in the normal-mode calculations. Thus, as listed in Table 2, we scale the computed wavenumbers by multiplication by a scaling factor c (0.983), which was obtained from a least-squares fit corresponding to the following formula 67 :…”
Section: Computational Detailsmentioning
confidence: 99%
“…This is probably due both to deficiencies in the electronic-structure level of theory used and to the neglect of anharmonicity, since the harmonic approximation is inherent in the normal-mode calculations. Thus, as listed in Table 2, we scale the computed wavenumbers by multiplication by a scaling factor c (0.983), which was obtained from a least-squares fit corresponding to the following formula 67 :…”
Section: Computational Detailsmentioning
confidence: 99%
“…The B3LYP functional and the 6-31G (d) basis sets were used and the optimizations were unconstrained. Vibrational frequencies of the normal modes were scaled by the standard scaling factor 0.96 [31].…”
Section: Analysis and Characterizationmentioning
confidence: 99%
“…Recently, discussions on the uncertainties in scaling factors for vibrational frequencies indicated that the values of the calculated frequencies can only have two significant figures. 40 Thus, the uncertainty of the individual frequency in the 2800-3000 cm -1 region can be as big as more than 50 cm -1 . Therefore, the theoretical results are shown here just for qualitative comparison with experiment and to interpret the spectra, and the sequence between the calculated overtone frequency of the bending mode and the fundamental stretching mode should not be taken literally.…”
Section: Theoretical Calculations Of Raman Spectra Of Gaseous Ethanolmentioning
confidence: 99%